Process Optimization for Development of Edible Plates Using By-products of Rice and Dhal Processing Industries - , Gouthami, N. S., Mathad, P. F., Udaykumar Nidoni., Sharanagouda Hiregoudar, Nagaraj, M. Naik (Archives of Current Research International, 2024)
Edible plates can be used as utensils to serve solids, semi-solids and highly viscous liquid food products whichare made out of food grains and are filled with various nutrients without any added preservatives.Edible plates from the rice bran flour (RBF), pigeonpeabrokens flour (PBF)and wheat flour (WF) were prepared by mixing in different proportions viz., 10, 15 and 20% of RBF, 20, 25 and 30% of PBF and the remaining proportion WF as the base material. Objective of this work is to evaluate the quality characteristics of developed edible plates. The optimized treatment was obtained with 20% of RBF, 30% of PBF and WF of 50%. The hardness and fracturability of the was found to be maximum (25.46 and 12.79 N) in T9. The tensile strength and elongation at break was also more in treatment T9 of 3.36 MPa and 2.13%. The tensile strength and elongation at break increased with the increase in supplementation level of by-products.